Investing in Maine’s Youngest Children Has Great Returns for Business - Connors, Dana (Maine Policy Review, 2009)
Dana F. Connors describes how the business community has become involved in the dialogue to help steer planning for investments in Maine’s youngest children. He acknowledges that there are high costs in failing to invest early and notes that creating skilled workers requires building the foundation in the first few years of the worker’s life. He stresses that high-quality early education and care are vital for both individual and statewide economic security.